Acute Demyelinating Polyradiculoneuropathy in Guillain-Barré Syndrome: A Case Report Highlighting Diagnostic Challenges and Management Strategies - Arumugam, Prathap; Thomas, Angelin Grace; Singam, Ann Jency Arul Durai; Palaniyappan, Dhivyaprasath (Indian Journal of Pharmacy Practice)
A 73-year-old female with fever, muscle weakness, and back pain was diagnosed with Acute Inflammatory Demyelinating Polyradiculoneuropathy (AIDP), a subtype of Guillain-Barré Syndrome (GBS). Laboratory findings showed elevated white blood cells, neutrophilia, and albuminocytological dissociation in cerebrospinal fluid. Nerve conduction studies confirmed demyelination, and imaging revealed degenerative spinal changes. She received Immunomodulatory therapy (IVIG) and supportive care, with careful management of comorbidities like hypertension and COPD. Early diagnosis and multidisciplinary care led to a positive outcome, highlighting the importance of timely intervention and monitoring to prevent complications and long-term disability.
Keywords: Electrodiagnostic; studies; Cerebrospinal; fluid; analysis; Immunotherapy; Rehabilitation; Nerve conduction studies